Meningkatkan Keberlanjutan Pariwisata Budaya melalui Partisipasi Komunitas Lokal: Kasus Istana Kesultanan Bima - Nurul Isti Qomah; Mustamin H Idris; Asfarony Hendra Naswim (Journal of Economics and Regional Science, 2024)
This study examines the role of community participation in sustaining the Asi Mbojo Museum, a cultural heritage site in Bima City, Indonesia. The museum plays a crucial role in preserving local history and enriching cultural awareness. Through a systematic literature review, 47 articles were identified from academic databases like Google Scholar and Scopus, with 6 articles directly relevant to the study. The findings underscore the significance of community involvement in museum management and development, influencing visitor numbers, economic benefits for locals, and cultural preservation. However, challenges such as limited access to information, financial resources, and infrastructure hinder community engagement. Enhancing community participation not only fosters sustainable tourism but also supports cultural heritage preservation and educational initiatives. This research highlights the imperative of community engagement strategies in promoting sustainable tourism practices and cultural heritage conservation in Bima City